Enhanced Ion Sieving of Graphene Oxide Membranes via Surface Amine Functionalization - Qian, Yijun; Shang, Jing; Liu, Dan; Yang, Guoliang; Wang, Xungai; Chen, Cheng; Kou, Liangzhi; Lei, Weiwei (Journal of the American Chemical Society, 2021)
Membranes based on two-dimensional (2D) nanomaterials have shown great potential to alleviate the worldwide freshwater crisis due to their outstanding performance of freshwater extraction from saline water via ion rejection. However, it is still very challenging to achieve high selectivity and high permeance of water desalination through precise d-spacing control of 2D nanomaterial membranes within subnanometer. Here, we developed functionalized graphene oxide membranes (FGOMs) with nitrogen groups such as amine groups and polarized nitrogen atoms to enhance metal ion sieving by one-step controlled plasma processing. The nitrogen functionalities can produce strong electrostatic interactions with metal ions and result in a mono/divalent cation selectivity of FGOMs up to 90 and 28.3 in single and binary solution, which is over 10-fold than that of graphene oxide membranes (GOMs). First-principles calculation confirms that the ionic selectivity of FGOMs is induced by the difference of binding energies between metal ions and polarized nitrogen atoms. Besides, the ultrathin FGOMs with a thickness of 50 nm can possess a high water flux of up to 120 mol m–2 h–1 without sacrificing rejection rates of nearly 99.0% on NaCl solution, showing an ultrahigh water/salt selectivity of around 4.31 × 103. Such facile and efficient plasma processing not only endows the GOMs with a promising future sustainable water purification, including ion separation and water desalination, but also provides a new strategy to functionalize 2D nanomaterial membranes for specific purposes.